Maternity benefit: comparison of systems and financing in V4 countries - Danuta DUDA; Kamila TUREČKOVÁ; Ivona BURYOVÁ; Radka KUBALOVÁ (Eastern Journal of European Studies, 2022)
Maternity leave is a standard social policy instrument implied in the family life of citizens of developed economies, but the actual scheme and conditions of the maternity leave and maternity benefit vary considerably from one country to another, even in the case of the usual regional units. Hence, the paper makes a deductive comparison of the individual maternity benefit systems in the V4 countries, specifying mutual similarities and partial differences, and processing them into an overview summary scheme. The descriptive part is complemented by an empirical analysis of the development of financing of maternity benefit within the social security systems in the period 2010-2019. The uniqueness of the elaborated topic lies in the absence of similar topics published so far, including the conclusion that Slovakia progressively approached the support of maternity through a significant financial and systemic strengthening of its status within its social system during the period under review.